2020
DOI: 10.6000/2292-2598.2020.08.03.13
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Environment as a Means of Forming Success of a Future Teacher of Elementary Classes in Project Activity

Abstract: Objective: The purpose of the study is to determine whether future elementary school teachers are successful in project activities and whether a properly organised collaborative environment affects the outcome of project activities.Background: In conditions when a person is the most important value and main capital of a society, the goal and product of the educational system should be human intelligence and personality. Therefore, for domestic education today, the issue of raising the status of the teaching pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…And this correlates with the data on the most important characteristic of a woman leader, according to the authors, is a high level of adaptability: the ability to understand what actions or approaches are needed in a given situation and then act accordingly. In this regard, a number of studies are devoted to the problem of developing personal qualities of women (professional mobility, the impact of the collective environment on pedagogical success) for future professional advancement [26,27]. Also, in the area, our research has shown that the leadership abilities of professionally successful women scientists correlate with such qualities as perseverance and volitional selfregulation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…And this correlates with the data on the most important characteristic of a woman leader, according to the authors, is a high level of adaptability: the ability to understand what actions or approaches are needed in a given situation and then act accordingly. In this regard, a number of studies are devoted to the problem of developing personal qualities of women (professional mobility, the impact of the collective environment on pedagogical success) for future professional advancement [26,27]. Also, in the area, our research has shown that the leadership abilities of professionally successful women scientists correlate with such qualities as perseverance and volitional selfregulation.…”
Section: Discussionmentioning
confidence: 85%
“…These requirements are as follows for women: to get a leadership position, a woman must demonstrate much greater competence. Because it is difficult, there are not many recognized women leaders [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The main purpose and focus of such training simulators is for the student to acquire the complex ability to make quick decisions. This skill is based on the direct ability to project active response of the simulated, considered object to the medical student's arbitrary interaction, particularly aimed at executive mechanisms (Shahrvini et al, 2021;Syzdykbayeva et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the organisation of the teaching process in modern higher educational institutions, which is responsible for the high-quality training of a new generation of professionals, is performed in a conventional. The intellectual and didactic potential of the current educational media space is still not in demand due to the low level of media competence among both students and teachers (Syzdykbayeva et al, 2020). The problem of developing the educational media space of the university to create the media competence among the student is of great importance both for pedagogy in general and for the system of higher professional education in particular.…”
Section: Literature Reviewmentioning
confidence: 99%